A different approach for solving singular two-point boundary value problems - İnç, Mustafa; Ergüt, M; Cherrulault, Y (Emerald Group Publishing Ltd, 2005)
Purpose - Aims to solve singular two-point boundary value problems, linear and non-linear by using modified and standard decomposition methods, respectively. Design/methodology/approach - The approximate solution of this problem is calculated in the form of series with easily computable components. Findings - The accuracy of the presented numerical method was examined in comparison with others and was found to be superior. Research limitations/implications - The decomposition method provided a reliable technique that required less work when compared with the traditional techniques. The method does not require unjustified assumptions linearisation discretizations or perturbation. Practical implications - The Adomian decomposition method was found to be very easy to apply to both differential equations, higher-order boundary value problems and linear or non-differential systems. Originality/value - The technique is both innovative and efficient and an original approach for solving singular two-point boundary value problems.
Keywords: cybernetics; polynomials; boundary-elements